Analysis the Effect of Total Liability on Net Income in PT. Pos Indonesia (Persero) - Shafira Cindy Meivianda (Journal of Contemporary Information Technology, Management, and Accounting, 2021)
Companies that want to expand their business, apart from using personal capital, can also seek external funds such as creditors. By increasing the liabilities / debt, it is expected that the company's performance will be much better so that it can get the desired net profit. The company's performance will also be said to be good if the profit generated is also good. With good profits and performance, the company can be glimpsed by investors. PT. Pos Indonesia (Persero) is an Indonesian State-Owned Enterprise (BUMN) which is engaged in postal services. This article will examine the effect of total debt or liability on net income at PT. Pos Indonesia (Persero). The result of this research is that there is no influence between liabilities / debts on the net income of PT. Pos Indonesia (Persero).